Fabrication of tungsten carbide–diamond composites using SiC-coated diamond - Kitiwan, Mettaya; Goto, Takashi (My University, 2019)
Tungsten carbide (WC) and SiC-coated diamond composites were prepared by spark plasma sintering at 1473–1873 K for 300 s under 130 MPa under vacuum. The diamond particle surface was coated with silicon carbide (SiC) via rotary chemical vapor deposition to improve the interfacial bonding of the WC–diamond composites. The relative density of the WC–20 vol% diamond (SiC) composite increased from 61% to 94% with increasing sintering temperature. Raman spectroscopic analysis showed that the diamond-to-graphite transition did not occur at any of the investigated sintering temperatures. The WC–20 vol% diamond composite sintered at 1773–1873 K exhibited high hardness (30.5 GPa) and fracture toughness (12.3 MPa m1/2). The high hardness resulted from the SiC coating functioning as an interlayer to improve the bonding between the diamond and WC body. The improvement in fracture toughness was attributed to the presence of diamond, which effectively blocks crack propagation and promotes crack deflection.
Keywords: Chemical vapor deposition; Diamond; Silicon carbide; Spark plasma sintering; Tungsten carbide